Synaptic Ultrastructure Might Be Involved in HCN1-Related BDNF mRNA in Withdrawal-Anxiety After Ethanol Dependence - Hou, Lanwei; Guo, Yujuan; Lian, Bo; Wang, Yanyu; Li, Changjiang; Wang, Gang; Li, Qi; Pang, Jinjing; Sun, Hongwei; Sun, Lin (Frontiers in Psychiatry, 2018)
Withdrawal from ethanol dependence has been associated with heightened anxiety and reduced expression of Brain-derived neurotropic factor which promotes the synaptic transmission and plasticity of synapses. Hyperpolarization-activated cyclic nucleotide-gated channel 1 regulates expression; however, whether Hyperpolarization-activated cyclic nucleotide-gated channel 1-related Brain-derived neurotropic factor is involved in the synaptic ultrastructure that generates withdrawal-anxiety has been poorly perceived. Sprague–Dawley rats were treated with ethanol 3-9% (v/v) for a period of 21 days. Conditioned place preference and body weight were investigated during ethanol administration. Rats were subjected to behavioral testing and biochemical assessments after ethanol withdrawal, which was induced by abrupt discontinuation of the treatment. The results showed that the ethanol administration induced severe ethanol dependence behaviors, with higher body weight and more time in the ethanol-paired compartment. After withdrawal, rats had a higher total ethanol withdrawal score and explored less. Additionally, increased Hyperpolarization-activated cyclic nucleotide-gated channel 1 protein and gene expression and decreased Brain-derived neurotropic factor protein and gene expression were detected in the Ethanol group. Eventually, there was a negative correlation between the level of   Brain-derived neurotropic factor mRNA and Hyperpolarization-activated cyclic nucleotide-gated channel 1 protein. Importantly, the synaptic ultrastructure changed in the Ethanol group, including increased synaptic cleft width and reduction in postsynaptic density thickness or synaptic curvature. The synthesis of the Brain-derived neurotropic factor mRNA could be down-regulated by higher Hyperpolarization-activated cyclic nucleotide-gated channel 1 protein expression. Changes in synaptic ultrastructure may be induced by lower Brain-derived neurotropic factor protein, which could be associated with the withdrawal-anxiety that is experiences after ethanol dependence.